A polar oxyhalogen-vanadate compound (C5NH13Cl)2VOCl4 with optical and two-staged dielectric switch behavior. Issue 26 (16th June 2021) - Kong, Qing-Rong; Wang, Bin; Liu, Xiao-Lin; Zhao, Hai-Xia; Long, La-Sheng; Zheng, Lan-Sun
Abstract : The polar compound (C5 NH13 Cl)2 VOCl4 was obtained based on polar anion [VOCl4 ] 2- . It exhibited optical and two-staged dielectric switch behavior. This work provides an optional method for constructing optic-dielectric switching materials. Abstract : Polar organic–inorganic hybrid materials have been applied in ferroelectricity, as well as in devices based on nonlinear optical and piezoelectricity properties. Here, we used a rectangular pyramid structure of [VOCl4 ] 2− to construct a polar compound (C5 NH13 Cl)2 VOCl4 (1 ). Compound 1 crystallized in the monoclinic P 21 space group. Coexistence of nonlinear optical switching behavior (space-group change from P 21 to P 21 / n ) and two-staged thermosensitive dielectric switching properties could be achieved under the stimulus of temperature. Our findings provide an effective approach for construction of polar materials.